Chemical priming of immunity without costs to plant growth. Issue 3 (21st February 2018) - Buswell, Will; Schwarzenbacher, Roland E.; Luna, Estrella; Sellwood, Matthew; Chen, Beining; Flors, Victor; Pétriacq, Pierre; Ton, Jurriaan
Summary: β‐Aminobutyric acid (BABA) induces broad‐spectrum disease resistance, but also represses plant growth, which has limited its exploitation in crop protection. BABA perception relies on binding to the aspartyl‐tRNA synthetase (AspRS) IBI1, which primes the enzyme for secondary defense activity. This study aimed to identify structural BABA analogues that induce resistance without stunting plant growth. Using site‐directed mutagenesis, we demonstrate that the (l )‐aspartic acid‐binding domain of IBI1 is critical for BABA perception. Based on interaction models of this domain, we screened a small library of structural BABA analogues for growth repression and induced resistance against biotrophic Hyaloperonospora arabidopsidis ( Hpa ). A range of resistance‐inducing compounds were identified, of which ( R )‐β‐homoserine (RBH) was the most effective. Surprisingly, RBH acted through different pathways than BABA. RBH‐induced resistance (RBH‐IR) against Hpa functioned independently of salicylic acid, partially relied on camalexin, and was associated with augmented cell wall defense. RBH‐IR against necrotrophic Plectosphaerella cucumerina acted via priming of ethylene and jasmonic acid defenses. RBH‐IR was also effective in tomato against Botrytis cinerea . Metabolic profiling revealed that RBH, unlike BABA, does not majorly affect plant metabolism. RBH primes distinct defense pathways against biotrophic and necrotrophic pathogens without stunting plant growth, signifying strong potential for exploitation in crop protection.